Donor‐derived renal allograft mucormycosis in a combined liver and kidney transplantation: Case report and review of the literature. Issue 3 (14th December 2020) - Thatipelli, Sneha; Santoiemma, Phillip; Echenique, Ignacio A.; Green, Richard; Ison, Michael G.; Ladner, Daniela; Kanwar, Yashpal S.; Stosor, Valentina
Abstract: Mucormycosis infrequently may present with isolated renal involvement. Among solid organ transplant recipients, renal allograft mucormycosis has been most often associated with medical tourism or transplantation outside of the western world. We report a case of an HIV/HCV co‐infected woman who underwent simultaneous liver and kidney transplantation with a Public Health Service increased risk donor organ. 16 days after transplant, she developed massive hematuria and was found to have renal allograft Rhizopus spp. involvement, we surmise to have been from donor‐derived infection. Therapy included nephrectomy, debridement, liposomal amphotericin B, and posaconazole with survival. We reviewed PubMed indexed, English‐language cases of isolated renal mucormycosis in general, in HIV/AIDS, and from donor‐derived renal allograft infections.